Small and medium-sized manufacturers’ ways of involving suppliers in digitally-enabled services - Momeni, Beheshte; Martinsuo, Miia; Härkälä, Jaakko (Emerald, 2024)
Purpose Information technology (IT) suppliers play a crucial role in shaping digitally-enabled services in small and medium-sized enterprises (SMEs) in the manufacturing sector, addressing limitations such as limited resources, a lack of digital expertise and financial constraints. This study investigates how manufacturing SMEs involve IT suppliers in digitally-enabled service offerings. Design/methodology/approach This paper investigates six manufacturing SMEs involving suppliers in digitally-enabled services. Data were collected via 20 in-depth interviews. Findings This study identifies SMEs’ sensing capabilities influencing their digitally-enabled services, including responding to industry and market demands, assessing customer readiness, developing responses to crises, and understanding IT suppliers’ offerings and capabilities. Three clusters of SMEs are introduced: operational efficiency seekers, service growth seekers and service-centric SMEs, based on their seizing capability through analyzing how different SMEs position services within the business strategy, allocate and manage service resources and build and leverage digital capabilities and readiness. These differ in how they involve IT suppliers: operational involvement, innovation collaboration and strategic partnership. Originality/value This research illuminates how digitally-enabled services and IT supplier involvement differ in SME environments. Analysis of SMEs’ digitally-enabled services and capabilities prompts a novel three-cluster framework. The findings unveil how manufacturing SMEs involve IT suppliers in digital servitization as it relates to the SMEs’ dynamic capabilities.
Keywords: Manufacturing SMEs; Digitally-enabled services; Supplier involvement; IT suppliers; fi=Strateginen johtaminen|en=Strategic Management|